A theory of political gridlock - Juan Ortner (Theoretical Economics, 2017)
This paper studies how electoral incentives influence the outcomes of political negotiations. It considers a game between two political parties that have to bargain over which policy to implement. While bargaining, the parties' popularity varies over time. Changes in popularity are partly exogenous and partly driven by the parties' actions. There is an election scheduled at a future date and the party with more popularity at the election date wins the vote. Electoral incentives can have substantial effects on bargaining outcomes. Periods of gridlock may arise when the election is close and parties have similar levels of popularity.
Keywords: C73; C78; D72; 330; Bargaining; elections; political gridlock; inefficient delay